2024
DOI: 10.1186/s12889-024-17853-y
|View full text |Cite
|
Sign up to set email alerts
|

Pornography, sexual orientation and ambivalent sexism in young adults in Spain

Belén Sanz-Barbero,
J. Francisco Estévez-García,
Raquel Madrona-Bonastre
et al.

Abstract: Background On line platforms offer access to an almost unlimited variety of pornographic material that shows high levels of sexism. Despite this fact, there are still few studies that assess the effect of pornography on sexism in young adults The aim of this study is to analyze the association of pornography consumption and sexual orientation with benevolent sexism (BS) and hostile sexism (HS) in young men and women. Methods We surveyed 2,346 peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…It perceives women as delicate entities needing male protection and endorses stereotypes that align with traditional views of femininity and gender roles. Some studies have found an association between the construct of sexism, especially hostile sexism, and the frequent use of pornographic material [ 15 , 16 ], while others have not established a consistent association between experimental exposure to pornography and sexism, and cross-sectional studies have found that pornography use is either unrelated to sexism or associated with more egalitarian beliefs regarding certain gender issues [ 2 , 17 ]. Another controversial issue is the role of pornography in the construction of masculinity.…”
Section: Introductionmentioning
confidence: 99%
“…It perceives women as delicate entities needing male protection and endorses stereotypes that align with traditional views of femininity and gender roles. Some studies have found an association between the construct of sexism, especially hostile sexism, and the frequent use of pornographic material [ 15 , 16 ], while others have not established a consistent association between experimental exposure to pornography and sexism, and cross-sectional studies have found that pornography use is either unrelated to sexism or associated with more egalitarian beliefs regarding certain gender issues [ 2 , 17 ]. Another controversial issue is the role of pornography in the construction of masculinity.…”
Section: Introductionmentioning
confidence: 99%